Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Achieving quality comfort care in nursing homes and long term care units through ambient assisted living (AAL) environments - Page, Robert; Richardson, Anthony S.; Coppola, Jean (International Journal of Interdisciplinary Research, 2016)
Nursing home administrators are caught in a "perfect storm" of rapidly increasing health care costs, decreasing reimbursement, and increasing competition. This paper documents how these pressures create cascading misalignments resulting in compromises of the quality of comfort care. These problems are inevitable, given the increase in unfunded mandates, where performance evaluation is decoupled from actual performance. Ambient technologies are explored as a means of tracking actual care versus reported care. Independent quality of care tracking and documentation of ambient data, coupled with best practice research and rewards, are explored to promote quality care as a marketing advantage. Implications are discussed.
Keywords: dept.bis; peer-reviewed

Evaluating the Knowledge of Conversational Agents - Park, Mina; Aiken, Milam; Vanjani, Mahesh (Southwestern Business Administration Journal, 2019)
Keywords: dept.bis; dept.mgt; peer-reviewed

College Students Understanding of Production Management and Master Production Schedule through Using a Real World Tool, Complimented with Company Tours and In- Class Visits, Provides an Excellent Learning Experience at Farmingdale State College - O'Sullivan, Jill (Journal of Systemics, Cybernetics and Informatics, 2015)
Manufacturing is playing a significant role in its re-shoring into America. Companies are grappling with ways to obtain that competitive advantage by distinguishing themselves through their intellectual capabilities, process improvements, technology, people, shop floor management and information flows. The purpose of this paper is to describe the effort at Farmingdale State College to educate our students in understanding Production Management and Master Production Schedule (MPS). We are trying to prepare students for entry into the workforce. By using a Real world ERP tool in the classroom while complimenting this learning with touring local manufacturers who use this tool and having production control experts in our classrooms. [1] The opportunity presents itself for these students to visit real world manufacturers using the same tool these students use in the classroom, the Infor Visual ERP. Each semester students go to a local manufacturer to see how the product is made and the ERP system is used to make it. Each semester a subject matter expert, SME, in manufacturing comes into the class and talks about how they use their ERP to perform their functional responsibilities. Students go into these companies and sit down with these Production Manufacturing and IT SME’s to see how they use the modules in their ERP system from estimating, Production Management, MPS to delivery and payment. From the manufacturing window to the Master Schedule Window students learn from these companies SME’s just how they perform their functions, how they use this tool. Then that is replicated this in the classroom lab assignments for students to better understand Production Management, scheduling and work order integrity. They identify the desired schedule (forecast) and populate a Master Production Schedule. They create a BOM with work orders adding operations and material. The Production Management/Control is the function of directing or regulating the movement of goods through the entire manufacturing cycle from the requisitioning of raw material to the delivery of finished products. (APICS Dictionary 13th Edition) The Master Production Schedule is often a major component of Sales and Operations Management. The purpose of the Master Schedule is to translate the Sales forecast into a Production Plan that must be executed by the organization. The Master Schedule is the demand side of the equation and must represent the customers’ needs. In this way the Master Scheduler can give manufacturing its best chance for success. Master Production Schedule (MPS): The MPS should be closely aligned with the Sales Forecast. Students enter a Sales Forecast into the system similar to what they have seen at the companies. Students see how it is the liaison between the Sales Forecast and a production work order. Its function is to translate the Sales Forecast into a viable production schedule that supports the customer requirements, while taking into account shop floor constraints. The MPS must support the Sales Forecast and customer demand. Students learn the importance of this in their lab assignments. They identify and enter shop floor resources. Students learn that companies should never chase supply they should chase demand and manage supply. Supply can mean, purchased parts, and externally produced parts, internally made items, internal machine or labor constraints. The student’s comprehension of this topic, concept and knowledge is significantly enhanced due to the tours to local manufacturers and the individuals that come into the class to discuss these functional areas and the processes they perform in their organizations.

Change Requires Change! Information Technology, Student Preparedness and Industry Collaboration: Supporting the Bridging Process between Education and Training with Innovative Solutions - O'Sullivan, Jill (Journal of Systemics, Cybernetics and Informatics, 2016)
This paper, Change Requires Change: will relate that bridging the gap between education: of what we teach and training: of what industry looks for in prepared skills for students, needs to be relevant to today’s situations. We need to re-evaluate traditional industry academic partnerships which have been relatively successful including; internships, work-study programs, curriculum advisory boards, guest lectures and capstone courses, to identify gaps and opportunities for what is needed to support our future. Do we want to continue with the status-quo or enhance education? Should we be cognizant of emerging trends? What could be the implications on changing academic-industry partnerships? How can we improve? This paper proposes several new approaches to academics and industry practitioner’s towards greater successful collaborations towards student preparation.
Keywords: dept.bis; peer-reviewed

Industry and Academic Partnership leads to Student Driven Success using an innovative Cloud Product in the classroom - O'Sullivan, Jill; Shahrier, Sayem (Journal of Systemics, Cybernetics and Informatics, 2018)
The relationships between Education/Training and Information Technologies at Farmingdale State College are accelerating, with the newest partnership involving the new CloudSuite Industrial Product, CSI, form Infor, USA, Inc. In this arrangement we have a dedicated Intern, Sayem Shahrier, a student at Farmingdale State College who assists with use of the CSI product in the classroom. According to this Intern, the implementation of the Infor CSI tool has been a great real life and hands-on experience. Students in the Education Alliance Program finally received a taste of how an ERP system works. Whether a company is big or small, it should be capable to manage and keep track of all their products and customers in real time. From local companies throughout Long Island all the way up to global mass markets have utilized the Infor CSI tool and have taken customer data to further maximize not only on profits but improve on operational excellence, customer intimacy, and the manufacturing process. Using this innovative tool and this partnership synergy, makes our students best prepared for industry entry and successes. This partnership brings together researchers and practitioners to support the bridging process between Education/Training and Information Technologies.
Keywords: dept.bis; peer-reviewed

Data mining and social networking sites: protecting business infrastructure and beyond - Bassett, Richard; Chamberlain, Tiffany; Cunningham, Stephen; Vidmar, Gregor (Issues in Information Systems, 2010)
Keywords: dept.bis; peer-reviewed

Sustainable Revenue Strategies for Enterprise Computing Solution Providers - Bassett, Richard A. (Research Yearbook, 2012)
Keywords: dept.bis; peer-reviewed

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Chatbots for Multilingual Conversations - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Journal of Management Science and Business Intelligence, 2019)
Chatbots emulate human dialogue to provide a more intuitive user interface to applications or simply provide entertainment. Chatbots rely on technology to function and new and emerging technologies such as NLP (Natural Language Processing) and AI (Artificial Intelligence) can be used to increase the ability of chatbots to emulate a more natural and free flowing conversation. As more and more mobile device users transition to increased use of texts and messaging chatbots can be used to provide consumers with multilingual support and services. While some chatbots have been developed in other languages, currently most converse only in English, and only a few can communicate in multiple languages. If configured correctly multilingual chatbots have the potential of providing a digital communication option that transcends language barriers. For our research we focused on the use of a chatbot that links the English-speaking Tutor Mike system with Google Translate, thus providing conversational capability in 103 languages, which is more than any other artificial multilingual agent is currently capable of. Two humans communicated with the system using German, Spanish, and Korean, and a group of undergraduate students reviewed the English translations of the chatbot’s replies. Results show that the responses from German and Spanish were cogent and natural, but those from Korean were less understandable. As a caveat, Asian languages lack much of the linguistic nuances of European languages. For example, there may be no plural form or gender in the Asian language. Unlike German where nouns and adjectives constantly change endings depending on what they are doing in a sentence and, unlike Spanish, which have numerous verb conjugations, Asian languages require no such changes. This might impact the translation ability and quality of a multilingual chatbot. Additional research and enhancements can improve chatbots used for European to Asian language translations and vice-versa. Regardless, our research shows promising results in the future use of multilingual chatbots to allow communication across the globe with business potential in the use of such chatbots to provide customer service and online live interaction with customers across the world.
Keywords: Chatbot, Multilingual, Communication, Machine Translation; dept.bis; dept.mgt; peer-reviewed

Automated translation preference with a bilingual chatbot - Park, Mina; Aiken, Milam (International Journal of Computers & Technology, 2019)
Free, online language translation services are being used by people around to the world to facilitate communication. However, it takes time and effort for a person to load the Web page in a browser, copy and paste text into the site, and translate words. The process quickly becomes tiresome. Instead, some computer programs are providing automated translation. However, no studies have been conducted to determine the efficiency or effectiveness of such an approach. In this study, we compare how students used an English-based chatbot with and without German automatic translation. Results show that students took nearly 1.5 times longer than their stated upper time limit to manually translate. In contrast, the automated translation was at least 30 times faster. In addition, the students were significantly more satisfied with the automated than the manual system.
Keywords: Chatbots; Google Translate; Tutor Mike; artificial conversation; dept.bis; dept.mgt; machine translation; peer-reviewed

A Study on Cloud Computing Adoption Within Small and Mid-Size Businesses (smbs) - Richardson, Anthony; Mate, Geoffrey (International Journal of Interdisciplinary Research, 2018)
A growing number of organizations have difficulty scaling-up their IT infrastructure to handle their growing needs and increased resource demands. Digital Technology Platforms (DTPs) have been identified by Gartner, Inc. as one of the top 10 strategic technology trends of 2017. While DTPs may be mainstream and easily adopted by large enterprise-sized organizations, there is an opportunity for such platforms within Small and Mid-Size Businesses (SMBs). The bottom line is that computing and server hardware is expensive for SMBs. Furthermore, it may be difficult for SMBs to assess and price the labor and resources needed for a company to have acceptable performance while controlling costs. The purpose of this paper is to examine how cloud computing technologies are adopted by SMBs and the respective drivers associated with costs and capability that may reduce costs for an organization. This paper explores how four variables – Robust Capability, Limited Capability, Cost Constraint, and Resource Abundance interact to impact the adoption of DTPs within SMBs. Adopters of DTPs are classified as Efficient, Proactive, Resistive, and Reactive. With respect to adoption efficacy, a model is proposed for assessing the capability and resource readiness as correlated to SMB adoption of DTPs. A study of 12 SMBs and the implementations of DTPs is presented and posited with the proposed adoption model. Due to the extensive investments required in procuring infrastructure services –adoption enablement is imperative for SMB-sized organizations to realize a return on investment. Implications are discussed.
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

How do humans interact with chatbots?: an analysis of transcripts - Park, Mina; Aiken, Milam; Salvador, Laura (International Journal of Management and Information Technology, 2018)
Keywords: dept.bis; dept.mgt; peer-reviewed